Mata dan Manusia Laut: Spirit Ekokritik dalam Sastra Anak - rizka amaliah (Raheema, 2022)
This article aims to examine the relationship between human with nature, God, and culture in children literature (Mata dan Manusia Laut novel) with the didactical element which creates awareness to preserve the environment since early stage. The approach that is used to analyze the discourse/narrative in the novel is one of postmodern intellectual product, which is ecocriticism – ecotheology. The result of this study indicates there is a connecting dot between science, social reality, and myth in the novel. The suprarational is told relevant to the concept of modern science, although criticism of myths also appears on the other side. Ecotheological conception which consists of four elements namely, taskhir, abd, khalifah, and amanah also appears in the narrative. The spirit of amanah even manifested in several activities (1) introspection, (2) mistake confession, (3) apology toward nature as an object of environmental damage, and (4) self-improvement behavior.